Outcomes Following Surgery for Complicated Tuberculosis: Analysis of 108 Patients - Bagheri, Reza; Haghi, Seyed Ziaollah; Rajabi, Mohammad Taghi Mashhadi; Motamedshariati, Mohammad; Sheibani, Shima (The Thoracic and Cardiovascular Surgeon, 2013)
Background Both incidence and complications of pleuropulmonary tuberculosis (TB) have increased due to recent increase of immunocompromising conditions. The aim of this study was to assess surgical outcomes in patients suffering from complicated pleuropulmonary TB.Methods This study included 108 patients with pleuropulmonary TB who underwent surgery. Age, sex, surgical indications, operative techniques, complications, mortality, and morbidity were evaluated.Results Male-female ratio was 1:11 with mean age of 40 years; 72.2 and 27.8% of the patients underwent surgery due to parenchymal and pleural complications. In the parenchymal group, the most common indication was parenchymal destruction (27.7%) and the most common procedure was lobectomy (50.9%). Out of 20 sputum smear-positive patients, 15 had multidrug-resistant tuberculosis (MDR-TB) and 5 had smear-positive open cavity. Overall 13 of the MDR-TB group and all smear-positive open cavity group became sputum-negative after the surgery. There were 13 patients with undiagnosed masses, among whom 3 patients had adenocarcinoma. In the pleural group, the most common surgical indication was empyema (13.8%) and the most common procedure was decortication and pleurectomy (13.8%). In the bronchopleural fistula group (6.4%), patients showed good results after surgery.There were 19.4% of patients who showed postoperative complications. The most common complication was residual space (5.5%). The main factors leading to major postoperative complications included positive preoperative sputum smear and history of immunocompromising condition. Mortality rate was 2.7%.Conclusion Considering the favorable results achieved by surgery in patients with pleuropulmonary TB, this treatment can be recommended for this group of patients.
Keywords: pleuropulmonary tuberculosis; diagnosis; treatment; complication